Development of lean construction framework for 'rumah komuniti' project - Hashim, Md Assri (2018)
Engaging in lean construction efforts could prove to be highly rewarding for Jabatan Pendidikan Kolej Komuniti (JPKK) and Kolej Komuniti Bandar Penawar. However, lean construction is risky and can be disastrous if not properly managed. Lean production efforts in some other firm construction have not been successful due to the many barriers to its successful implementation. To enable lean construction efforts and to increase the chances of success in eliminating waste, a thorough study of the lean practice or lean conformance is essential. Structured questionnaire were carried out to assess their perception of lean conformance based on their experience to build ‘Rumah Komuniti’. The lean conformance influenced by sub principles Culture/people, Continuous improvement, customer focus, eliminate waste and Standardization. The obtained information from the data was analysed using descriptive analysis with mean respectively 3.9917, 3.8438, 4.0750, 3.9764 and 4.0542. The proposed Lean Construction Framework in this study is generic and can be applied to any type of work.